Caspase inhibition mitigates tau cleavage and neurotoxicity in iPSC‐induced neurons with the V337M MAPT mutation. (1st February 2022) - Theofilas, Panos; Ambrose, Andrew J.; Butler, David; Wang, Chao; Morales, Dulce O.; Petersen, Cathrine; Chin, Brian; Yang, Teddy; Khan, Shireen; Ng, Raymond; Kayed, Rakez; Karch, Celeste M.; et al.
Abstract: Background: Tau post‐translational modifications (PTMs) are associated with progressive tau accumulation and neuronal loss in tauopathies, including forms of frontotemporal lobar degeneration (FTLD) and Alzheimer's disease (AD). Proteolytic cleavage of tau by active caspases, including caspase‐6, represents an underexplored tau PTM implicated in tau pathology by generating tau species with an enhanced propensity for self‐aggregation and accumulation into neuronal cytoplasmic inclusions. Method: To elucidate the presence and temporal course of caspase activation, tau cleavage, and neuronal death, we generated two neoepitope monoclonal antibodies (mAbs) against caspase‐6 tau proteolytic sites (D13 and D402) and cortical neurons (iNs) from induced pluripotent stem cells (iPSCs) with the frontotemporal dementia (FTD)‐causing V337M  MAPT  mutation (tau V337M ). Result: FTLD tau V337M  and AD postmortem brains showed positivity for both cleaved tau mAbs as well as active caspase‐6 (Fig. 1). Three month tau V337M  iNs showed a three‐fold increase in caspase‐cleaved D402 and D13 tau protein levels and increased p‐tau and oligomeric tau species compared to controls (Fig. 2). Three month tau V337M  iNs also showed a significantly higher rate of neuronal death than the tau WT  counterpart. Treatment with staurosporine (STS), a stress inducer, led to a 5‐fold increase of cytotoxicity levels in STS‐treated tau V337M  iNs compared to vehicle‐treated tau V337M  iNs. Although STS‐induced cytotoxicity was anticipated, the increase was significantly higher in STS‐treated tau V337M  iNs than in STS‐treated control iNs. Similarly, we observed a 4‐fold increase of caspase‐6 activity in STS‐treated tau V337M  iNs compared to vehicle‐treated tau V337M  iNs that was reversed following co‐treatment with the caspase‐6 inhibitor z‐VEID‐fmk (Fig. 2). Conclusion: We propose a model in which time‐dependent accumulation of caspase‐cleaved tau in V337M  MAPT  neurons promotes neurotoxicity that is reversed by caspase‐6 inhibition. Caspase‐cleaved tau may be a biomarker of tauopathy, and caspases could be viable targets for therapeutic intervention against tau pathogenesis in FTLD and other tauopathies.